A Volume-of-Fluid Heat Pipe Model Resolving Pressure Discontinuities at the Wick-Vapor Interface. (15th September 2022) - Zimmermann, Sascha; Klippel, Maximilian; Dreiling, Robert; Nguyen-Xuan, Thinh; Pfitzner, Michael
Highlights: A novel Volume-of-Fluid based method for calculating heat pipe performance is presented Temperature and pressure discontinuities at the wick-vapor interface are resolved Momentum sources account for the flow resistance within the wick This paper reveals a methodical error in the state-of-the-art simulation approach The model yields precise results with reasonable computational effort Abstract: Heat pipes are passive cooling devices which play an increasingly important role in a vast field of cooling solutions for technologies like electric machines or consumer electronics. Simulations that reliably predict the heat pipe's performance and operational limits are the key for optimizing cooling efficiency. In this paper, a novel Volume-of-Fluid model is presented which resolves temperature and pressure discontinuities at the wick-vapor interface. The flow resistance in the wick structure is modeled using momentum sources based on the Darcy-Forchheimer formulation. Additional momentum sources perpendicular to the phase boundary account for capillary forces and ultimately lead to distinct pressure regimes in the wick and vapor flow. Evaporation and condensation are modeled using a data set which takes wick microstructure effects into account and is based on statistic rate theory. The involved thermophysical fluid properties are obtained from a model by the International Association for the Properties of Water and Steam depending on temperature and pressure. Eventually, the simulation approach is validated against experimental and numerical data from literature. The final model enables thermal engineers to predict dry-out conditions and to optimize the capillary structure and heat pipe geometry. Furthermore, this paper reveals a methodical error in the state-of-the-art simulation approach which leads to a significant underestimation of mass flow and pressure drop.